Software Architecture Hour with Neal Ford. (O'Reilly Media, Inc., 2023)
Join us for a special conversation with Neal Ford and Thoughtworks tech principal Andrew Harmel-Law about how the definition of an "effective" software architect is changing in response to the rise of modern decoupled systems. Architects, and traditional architectural approaches, must evolve to meet the challenges of increasingly autonomous, independent, and self-managing development teams. You can avoid creating the bottleneck for architecture decisions when you're working with all those teams. Andrew will outline the architecture advice process, which enables anyone working in a system to make an architecture decision--but only after talking to the people who have expertise as well as the people who'll be impacted by the decision. This is a chance for you to hear from Neal and Andrew about software, architecture, and their own career journeys. They'll spend a few minutes covering the trends that are influencing architecture, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it How to craft technical strategy and make sure it's aligned to business needs See what's coming next with software architecture This recording of a live event is for you because... You want the chance to hear from Neal Ford and Andrew Harmel-Law about software design, extreme programming, and what the future might look like. You are currently looking for ways to grow your own skills and to act as an innovator in your organization. Recommended follow-up: Read Software Architecture: The Hard Parts (book) Listen to The Software Architect Elevator (audiobook) Read Building Evolutionary Architectures, second edition (book) Read Software Architecture Metrics (book).